Analysis of Population Administration Service Quality in Kelurahan Triwung, Probolinggo City - Supriyanto Supriyanto; Andhi Nur Rahmadi; Mohammad Ridwan (The Future of Education Journal, 2026)
Population administration service, including the issuance of Identity Cards (KTP), Family Cards (KK), birth certificates, and death certificates, is a form of public service that directly affects the daily needs of the community, with the sub-district (kelurahan) playing a strategic role as the government unit closest to the people. This study aims to analyze the quality of population administration services at Kelurahan Triwung, Probolinggo City, and to identify the supporting and inhibiting factors in its implementation. This research used a descriptive qualitative method, with data collected through observation, interviews, and documentation involving the sub-district head, staff, population administration officers, and community members as key informants, then analyzed through data reduction, data display, and conclusion drawing. Service quality was assessed using the SERVQUAL theory developed by Parasuraman, Zeithaml, and Berry (1988), covering five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that service quality at Kelurahan Triwung has generally run well across all five dimensions: adequate facilities and disability-friendly access (tangibles), procedures carried out in accordance with regulations (reliability), prompt responses and coordination with the Population and Civil Registration Office (responsiveness), certainty of procedures and document security (assurance), and friendly, non-discriminatory attitudes toward the community (empathy). However, limited public understanding of administrative requirements remains an obstacle affecting service speed and accuracy. Continuous efforts, such as public education, improved information systems, and staff capacity building, are needed to achieve more optimal, transparent, and accountable public service.